High-strength cordierite-mullite ceramic tube and preparation process thereof
By using the preparation process of high-strength cordierite-mullite ceramic tubes in the manufacturing of ceramic tubes, the problems of pores and cracks in ceramic tubes are solved, and the high strength and toughness of ceramic tubes are achieved, which improves its performance stability.
Patent Information
- Application Number
- CN202411731735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
During the manufacturing process of ceramic tubes, gases in the raw materials cannot be completely discharged, resulting in the formation of pores and reducing the strength of the ceramic tubes; at the same time, stress concentration, material layer separation and uneven cooling in the molding step lead to cracks, further reducing strength and toughness.
The preparation process of high-strength cordierite-mullite ceramic tubes is adopted, including mixing mullite, cordierite, alumina and sintering additives in a specific proportion, and pressing them through isostatic pressing equipment to form the ceramic tube embryo. Then, presintering, sputtering vacuum coating and vacuum high-temperature sintering are performed to form high-strength ceramic tubes.
Through this process, ceramic tubes achieve better sintering effect at lower temperatures, enhancing the overall strength and toughness of ceramic tubes, avoiding the formation of pores and cracks, and significantly improving the performance stability of ceramic tubes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ceramic tube preparation, and more specifically, to a high-strength cordierite-mullite ceramic tube and a preparation process thereof. Background Art
[0002] Ceramic materials are a type of inorganic non-metallic materials made from natural or synthetic compounds through molding and high-temperature sintering. Ceramic tubes are tubular devices made of ceramic materials. Due to the unique physical and chemical properties of ceramic materials, ceramic tubes are widely used in many fields, such as electronic components, chemical industry, medical treatment, machinery manufacturing, etc.
[0003] Ceramic tubes face the following problems during the manufacturing process: 1. During the manufacturing process of ceramic tubes, the gas in the raw materials cannot be completely discharged, and there are often pores in the mold, which leads to the formation of pores on the surface or inside the ceramic tube. The pores will reduce the strength of the ceramic tube and thus affect the performance of the ceramic tube. 2. During the manufacturing process of ceramic tubes, stress concentration, material layer separation, and uneven cooling in the forming step will cause cracks in the ceramic tube, which will reduce the strength and toughness of the ceramic tube.
[0004] Based on the above statements, the present application provides a high-strength cordierite-mullite ceramic tube and a preparation process thereof. Summary of the invention
[0005] In order to solve the problems raised by the background technology, the present application provides a high-strength cordierite-mullite ceramic tube and a preparation process thereof.
[0006] In the first aspect, the present application provides a high-strength cordierite-mullite ceramic tube, which adopts the following technical solution: A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 20-40 parts of mullite, 20-30 parts of cordierite, 12-16 parts of alumina, and 0.4-1 part of a sintering aid.
[0007] Preferably, the particle size of the mullite is 1-10 μm, the particle size of the cordierite is 1-3 mm, and the alumina is α-alumina with a particle size of 5-10 μm.
[0008] Preferably, the sintering aid is prepared as follows: adding nano lithium silicate to a boric acid solution with a mass concentration of 10-20%, ultrasonically dispersing to obtain a dispersion, adding a silane coupling agent to the dispersion, ultrasonically dispersing to obtain a sintering aid.
[0009] Preferably, the mass ratio of the nano-lithium cobalt oxide to the boric acid solution is 1:2-4; the mass ratio of the silane coupling agent to the dispersion is 1:20-30; and the silane coupling agent is an epoxy silane coupling agent.
[0010] In a second aspect, the present application provides a preparation process of a high-strength cordierite-mullite ceramic tube, using the following technical solution: A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, mixing and stirring the raw materials by weight to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; S3, pre-sintering the ceramic tube embryo, and obtaining a pre-sintered ceramic tube embryo after natural cooling; S4, coating the surface of the pre-sintered ceramic tube embryo body by sputtering vacuum coating method, placing the coated ceramic tube embryo body in a curing liquid for vacuum infiltration and curing, taking it out and drying it to obtain a coated ceramic tube embryo body; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube.
[0011] Preferably, the pressing conditions of the medium static pressure equipment in step S2 are: pressure of 150-350 MPa, and pressing time of 2-6 min.
[0012] Preferably, the pre-sintering temperature is 1200-1300° C., and the pre-sintering time is 0.5-1 h.
[0013] Preferably, the coating material in step S4 is potassium hexatitanate whiskers with a particle size of 30-50 nm, and the vacuum degree of sputtering vacuum coating is 9×10 -7 -11×10 -7 Pa, sputtering power is 100-200w, and film thickness is 5-10μm.
[0014] Preferably, the curing liquid in step S4 is a polymethylsilane solution with a mass concentration of 10-16%, and the curing time is 1-2 hours.
[0015] Preferably, the sintering conditions in step S5 are: sintering temperature is 1650-1750° C., and sintering time is 4-6 hours.
[0016] In summary, this application has the following beneficial effects: 1. The present application adds nano lithium silicate to a boric acid solution, disperses it ultrasonically, and obtains a dispersion liquid. A silane coupling agent is added to the dispersion liquid, disperses it ultrasonically, and obtains a sintering aid. Boric acid can reduce the sintering temperature of ceramics, while lithium silicate can enhance the sintering performance of ceramics. The combined effect of the two can enable the ceramic tube to achieve a better sintering effect at a lower temperature.
[0017] 2. In the preparation process of the ceramic tube, the pre-sintered ceramic is coated on the surface by sputtering vacuum coating method. The coating material is potassium hexatitanate whiskers. The coated ceramic tube is placed in a curing liquid for vacuum infiltration and curing. The curing liquid is a polymethylsilane solution. Both the potassium hexatitanate whiskers and the polymethylsilane cured film have high thermal stability. Their synergistic effect can further enhance the performance stability of the ceramic tube in a high temperature environment and prevent cracking or deformation caused by thermal stress. The potassium hexatitanate whisker coating and the polymethylsilane cured film form a composite reinforcement structure on the surface of the ceramic tube. This composite structure can more effectively absorb and disperse the energy under the action of external forces, thereby improving the overall strength and toughness of the ceramic tube.
[0018] 3. The cordierite-mullite ceramic tube prepared in the present application has the beneficial effects of high stability, high strength and high toughness. DETAILED DESCRIPTION
[0019] The present application is further described in detail below with reference to the embodiments.
[0020] Embodiment 1-3 provides a high-strength cordierite-mullite ceramic tube and a preparation process thereof.
[0021] Example 1 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 20 parts of mullite, 20 parts of cordierite, 12 parts of alumina, and 0.4 parts of sintering aid.
[0022] The particle size of mullite is 1 μm, the particle size of cordierite is 1 mm, and the alumina is α-alumina with a particle size of 5 μm.
[0023] The sintering aid is prepared as follows: nano lithium silicate is added to a boric acid solution with a mass concentration of 10%, and ultrasonically dispersed at a frequency of 100kHz for 0.5h to obtain a dispersion, and γ-glycidyloxypropyl triethoxysilane is added to the dispersion, and ultrasonically dispersed at a frequency of 100kHz for 0.5h to obtain a sintering aid. The mass ratio of nano lithium cobaltate to the boric acid solution is 1:2; the mass ratio of γ-glycidyloxypropyl triethoxysilane to the dispersion is 1:20.
[0024] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 80 rpm for 1 h to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 150 MPa and a pressing time of 2 min; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1200° C., and the pre-sintering time is 0.5 h; S4, coating the surface of the pre-sintered ceramic tube embryo by sputtering vacuum coating method, placing it in a curing liquid for vacuum infiltration and curing after coating, taking it out and placing it in a 50°C oven for drying for 6 hours to obtain a coated ceramic tube embryo; wherein the coating material is potassium hexatitanate whisker with a particle size of 30nm, and the vacuum degree of sputtering vacuum coating is 9×10 -7 Pa, the sputtering power is 100w, the film thickness is 5μm; the curing liquid is a polymethylsilane solution with a mass concentration of 10%, and the curing time is 1h; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; wherein the sintering conditions are: the sintering temperature is 1650° C., and the sintering time is 4 hours.
[0025] Example 2 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 30 parts of mullite, 25 parts of cordierite, 14 parts of alumina, and 0.7 parts of sintering aid.
[0026] The particle size of mullite is 5 μm, the particle size of cordierite is 2 mm, and the alumina is α-alumina with a particle size of 8 μm.
[0027] The sintering aid was prepared as follows: nano lithium silicate was added to a boric acid solution with a mass concentration of 15%, and ultrasonically dispersed at a frequency of 110kHz for 0.8h to obtain a dispersion, and γ-glycidyloxypropyltriethoxysilane was added to the dispersion, and ultrasonically dispersed at a frequency of 110kHz for 0.8h to obtain a sintering aid. The mass ratio of nano lithium cobaltate to the boric acid solution was 1:3; the mass ratio of γ-glycidyloxypropyltriethoxysilane to the dispersion was 1:25.
[0028] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 100 rpm for 2 h to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 250 MPa and a pressing time of 4 minutes; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1250° C., and the pre-sintering time is 0.8 h; S4, coating the surface of the pre-sintered ceramic tube embryo by sputtering vacuum coating method, placing it in a curing liquid for vacuum infiltration and curing after coating, taking it out and placing it in a 50°C oven for drying for 6 hours to obtain a coated ceramic tube embryo; wherein the coating material is potassium hexatitanate whisker with a particle size of 40nm, and the vacuum degree of sputtering vacuum coating is 10×10 -7 , the sputtering power is 150w, the film thickness is 8μm; the curing liquid is a polymethylsilane solution with a mass concentration of 13%, and the curing time is 1.5h; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; wherein the sintering conditions are: the sintering temperature is 1700° C., and the sintering time is 5 hours.
[0029] Example 3 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 40 parts of mullite, 30 parts of cordierite, 16 parts of alumina, and 1 part of sintering aid.
[0030] The particle size of mullite is 10 μm, the particle size of cordierite is 3 mm, and the alumina is α-alumina with a particle size of 10 μm.
[0031] The sintering aid was prepared as follows: nano lithium silicate was added to a boric acid solution with a mass concentration of 20%, and ultrasonically dispersed at a frequency of 120kHz for 1 hour to obtain a dispersion, and γ-glycidyloxypropyltriethoxysilane was added to the dispersion, and ultrasonically dispersed at a frequency of 120kHz for 1 hour to obtain a sintering aid. The mass ratio of nano lithium cobaltate to the boric acid solution was 1:4; the mass ratio of γ-glycidyloxypropyltriethoxysilane to the dispersion was 1:30.
[0032] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 120 rpm for 3 hours to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 350 MPa and a pressing time of 6 minutes; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1300° C., and the pre-sintering time is 1 hour; S4, coating the surface of the pre-sintered ceramic tube embryo by sputtering vacuum coating method, placing it in a curing liquid for vacuum infiltration and curing after coating, taking it out and drying it in a 50°C oven for 6 hours to obtain a coated ceramic tube embryo; wherein the coating material is potassium hexatitanate whisker with a particle size of 50nm, and the vacuum degree of sputtering vacuum coating is 11×10 -7Pa, the sputtering power is 200w, the film thickness is 10μm; the curing liquid is a polymethylsilane solution with a mass concentration of 16%, and the curing time is 2h; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; sintering conditions: wherein the sintering temperature is 1750° C. and the sintering time is 6 hours.
[0033] In order to verify the comprehensive performance of the high-strength cordierite-mullite ceramic tubes prepared in Examples 1-3 of the present application, the applicant set up Comparative Examples 1-4, which are as follows: Comparative Example 1 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 20 parts of mullite, 20 parts of cordierite, 12 parts of alumina, and 0.4 parts of sintering aid.
[0034] The particle size of mullite is 1 μm, the particle size of cordierite is 1 mm, and the alumina is α-alumina with a particle size of 5 μm.
[0035] The sintering aid is prepared as follows: γ-glycidyloxypropyltriethoxysilane is added to a boric acid solution with a mass concentration of 10%, and ultrasonically dispersed at a frequency of 100 kHz for 0.5 h to obtain a sintering aid, wherein the mass ratio of γ-glycidyloxypropyltriethoxysilane to the boric acid solution is 1:20.
[0036] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 80 rpm for 1 h to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 150 MPa and a pressing time of 2 min; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1200° C., and the pre-sintering time is 0.5 h; S4, coating the surface of the pre-sintered ceramic tube embryo by sputtering vacuum coating method, placing it in a curing liquid for vacuum infiltration and curing after coating, taking it out and placing it in a 50°C oven for drying for 6 hours to obtain a coated ceramic tube embryo; wherein the coating material is potassium hexatitanate whisker with a particle size of 30nm, and the vacuum degree of sputtering vacuum coating is 9×10 -7 Pa, the sputtering power is 100w, the film thickness is 5μm; the curing liquid is a polymethylsilane solution with a mass concentration of 10%, and the curing time is 1h; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; wherein the sintering conditions are: the sintering temperature is 1650° C., and the sintering time is 4 hours.
[0037] Comparative Example 2 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 20 parts of mullite, 20 parts of cordierite, 12 parts of alumina, and 0.4 parts of sintering aid.
[0038] The particle size of mullite is 1 μm, the particle size of cordierite is 1 mm, and the alumina is α-alumina with a particle size of 5 μm.
[0039] The sintering aid is prepared as follows: nano lithium silicate is added to distilled water, ultrasonically dispersed at a frequency of 100 kHz for 0.5 h to obtain a dispersion, and γ-glycidyloxypropyl triethoxysilane is added to the dispersion, ultrasonically dispersed at a frequency of 100 kHz for 0.5 h to obtain a sintering aid. The mass ratio of nano lithium cobaltate to distilled water is 1:2; the mass ratio of γ-glycidyloxypropyl triethoxysilane to the dispersion is 1:20.
[0040] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 80 rpm for 1 h to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 150 MPa and a pressing time of 2 min; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1200° C., and the pre-sintering time is 0.5 h; S4, coating the surface of the pre-sintered ceramic tube embryo by sputtering vacuum coating method, placing it in a curing liquid for vacuum infiltration and curing after coating, taking it out and placing it in a 50°C oven for drying for 6 hours to obtain a coated ceramic tube embryo; wherein the coating material is potassium hexatitanate whisker with a particle size of 30nm, and the vacuum degree of sputtering vacuum coating is 9×10 -7 Pa, the sputtering power is 100w, the film thickness is 5μm; the curing liquid is a polymethylsilane solution with a mass concentration of 10%, and the curing time is 1h; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; wherein the sintering conditions are: the sintering temperature is 1650° C., and the sintering time is 4 hours.
[0041] Comparative Example 3 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 20 parts of mullite, 20 parts of cordierite, 12 parts of alumina, and 0.4 parts of sintering aid.
[0042] The particle size of mullite is 1 μm, the particle size of cordierite is 1 mm, and the alumina is α-alumina with a particle size of 5 μm.
[0043] The sintering aid is prepared as follows: nano lithium silicate is added to a boric acid solution with a mass concentration of 10%, and ultrasonically dispersed at a frequency of 100kHz for 0.5h to obtain a dispersion, and γ-glycidyloxypropyl triethoxysilane is added to the dispersion, and ultrasonically dispersed at a frequency of 100kHz for 0.5h to obtain a sintering aid. The mass ratio of nano lithium cobaltate to the boric acid solution is 1:2; the mass ratio of γ-glycidyloxypropyl triethoxysilane to the dispersion is 1:20.
[0044] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 80 rpm for 1 h to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 150 MPa and a pressing time of 2 min; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1200° C., and the pre-sintering time is 0.5 h; S4, placing the pre-sintered ceramic tube embryo body in a curing liquid for vacuum infiltration curing, taking it out and placing it in a 50° C. oven for drying for 6 hours to obtain a coated ceramic tube embryo body; wherein the curing liquid is a polymethylsilane solution with a mass concentration of 10%, and the curing time is 1 hour; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; wherein the sintering conditions are: the sintering temperature is 1650° C., and the sintering time is 4 hours.
[0045] Comparative Example 4 A high-strength cordierite-mullite ceramic tube comprises the following raw materials in parts by weight: 20 parts of mullite, 20 parts of cordierite, 12 parts of alumina, and 0.4 parts of sintering aid.
[0046] The particle size of mullite is 1 μm, the particle size of cordierite is 1 mm, and the alumina is α-alumina with a particle size of 5 μm.
[0047] The sintering aid is prepared as follows: nano lithium silicate is added to a boric acid solution with a mass concentration of 10%, and ultrasonically dispersed at a frequency of 100kHz for 0.5h to obtain a dispersion, and γ-glycidyloxypropyl triethoxysilane is added to the dispersion, and ultrasonically dispersed at a frequency of 100kHz for 0.5h to obtain a sintering aid. The mass ratio of nano lithium cobaltate to the boric acid solution is 1:2; the mass ratio of γ-glycidyloxypropyl triethoxysilane to the dispersion is 1:20.
[0048] A preparation process of a high-strength cordierite-mullite ceramic tube comprises the following steps: S1, stirring and mixing the raw materials by weight at a rate of 80 rpm for 1 h to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; wherein the pressing conditions of the isostatic pressing device are: a pressure of 150 MPa and a pressing time of 2 min; S3, pre-sintering the ceramic tube embryo, and naturally cooling it to room temperature to obtain a pre-sintered ceramic tube embryo; wherein the pre-sintering conditions are: the pre-sintering temperature is 1200° C., and the pre-sintering time is 0.5 h; S4, coating the surface of the pre-sintered ceramic tube embryo body by sputtering vacuum coating method to obtain a coated ceramic tube embryo body; wherein the coating material is potassium hexatitanate whisker with a particle size of 30nm, and the vacuum degree of sputtering vacuum coating is 9×10 -7 Pa, sputtering power is 100w, film thickness is 5μm; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube; wherein the sintering conditions are: the sintering temperature is 1650° C., and the sintering time is 4 hours.
[0049] Performance Testing The comprehensive properties of the high-strength cordierite-mullite ceramic tubes prepared in Examples 1-3 of the present application and Comparative Examples 1-4 were tested respectively.
[0050] The mechanical strength of the high-strength cordierite-mullite ceramic tubes prepared in Examples 1-3 and Comparative Examples 1-4 was tested in accordance with GB / T 4740-1999. The results are shown in Table 1: Table 1
[0051] From the data shown in Table 1, it can be seen that the comprehensive performance of the high-strength cordierite-mullite ceramic tubes prepared in Examples 1-3 is far superior to that of Comparative Examples 1-4. The high-strength cordierite-mullite ceramic tubes prepared in Examples 1-3 have high bending strength and high fracture toughness.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength cordierite-mullite ceramic tube, characterized in that: The invention comprises the following raw materials in parts by weight: 20-40 parts of mullite, 20-30 parts of cordierite, 12-16 parts of alumina and 0.4-1 part of a sintering aid.
2. The high-strength cordierite-mullite ceramic tube according to claim 1, characterized in that: The particle size of the mullite is 1-10 μm, the particle size of the cordierite is 1-3 mm, and the alumina is α-alumina with a particle size of 5-10 μm.
3. The high-strength cordierite-mullite ceramic tube according to claim 1, characterized in that: The sintering aid is prepared as follows: adding nano lithium silicate to a boric acid solution with a mass concentration of 10-20%, ultrasonically dispersing to obtain a dispersion, adding a silane coupling agent to the dispersion, ultrasonically dispersing to obtain the sintering aid.
4. The high-strength cordierite-mullite ceramic tube according to claim 3, characterized in that: The mass ratio of the nano lithium cobalt oxide to the boric acid solution is 1:2-4; the mass ratio of the silane coupling agent to the dispersion is 1:20-30; and the silane coupling agent is an epoxy silane coupling agent.
5. A process for preparing the high-strength cordierite-mullite ceramic tube according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing and stirring the raw materials by weight to obtain a mixture; S2, placing the mixture in an isostatic pressing device to obtain a ceramic tube embryo; S3, pre-sintering the ceramic tube embryo, and obtaining a pre-sintered ceramic tube embryo after natural cooling; S4, coating the surface of the pre-sintered ceramic tube embryo body by sputtering vacuum coating method, placing the coated ceramic tube embryo body in a curing liquid for vacuum infiltration and curing, taking it out and drying it to obtain a coated ceramic tube embryo body; S5. Place the coated ceramic tube embryo in a vacuum high-temperature sintering furnace for sintering to obtain a high-strength cordierite-mullite ceramic tube.
6. The process for preparing the high-strength cordierite-mullite ceramic tube according to claim 5, characterized in that: The pressing conditions of the medium static pressure equipment in step S2 are: pressure of 150-350 MPa, and pressing time of 2-6 min.
7. The process for preparing the high-strength cordierite-mullite ceramic tube according to claim 5, characterized in that: The pre-sintering conditions in step S3 are as follows: the pre-sintering temperature is 1200-1300° C., and the pre-sintering time is 0.5-1 h.
8. The process for preparing the high-strength cordierite-mullite ceramic tube according to claim 5, characterized in that: The coating material in step S4 is potassium hexatitanate whiskers with a particle size of 30-50 nm, and the vacuum degree of sputtering vacuum coating is 9×10 -7 -11×10 -7 Pa, sputtering power is 100-200w, and film thickness is 5-10μm.
9. The process for preparing the high-strength cordierite-mullite ceramic tube according to claim 5, characterized in that: In step S4, the curing liquid is a polymethylsilane solution with a mass concentration of 10-16%, and the curing time is 1-2 hours.
10. The process for preparing the high-strength cordierite-mullite ceramic tube according to claim 5, characterized in that: The sintering conditions in step S5 are as follows: the sintering temperature is 1650-1750° C., and the sintering time is 4-6 hours.
Citation Information
Patent Citations
Preparing method of abrasion-resistant and corrosion-resistant transparent aluminum oxide ceramic tube
CN105777205A
Sintering supporting body and manufacturing method thereof
CN106242603A
Fire-proof crucible for sintering of cathode material for lithium battery and preparation method of fire-proof crucible
CN109400137A
Sagger for roasting lithium battery positive electrode material and preparation method thereof
CN112759377A
Sagger for positive electrode material of lithium battery and preparation method of sagger
CN116621591A